(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
In this article, in order to stabilize the financial situation of prestigious companies in the world, create new jobs and achieve economic growth, it is necessary to "transition to international standards of management, use transfer pricing in the process of concluding financial transactions in entities of the cluster and cooperative system, and present financial and management reports on operational segments." . International experience testifies to the fact that a sufficient information base has been formed on the theoretical, methodological and organizational aspects of these problems, and special scientific and innovative research is being conducted in this regard. According to the research, "US Federal Tax Service (IRS) received 3.4 billion dollars obtained as a result of illegal allocation of royalties and other costs in the process of trade deals between UK and US companies in the process of formation of transfer pricing." that dollar income was returned to the main company located in England" indicates the seriousness and importance of the issue.